Submucosal lipoma simulating a malignant tumor of the left colon: a case report - Campos,Victor Minari (2016)
ABSTRACT Intestinal lipomas can occur anywhere in the gastrointestinal tract, and these tumors are more frequent in the colon. By being largely asymptomatic, colonic lipomas are usually found incidentally, as findings in colonoscopy examinations, in association with biopsy. Endoscopic or surgical resection is the therapeutic option, depending on the size of the tumor, its location, and the presence or absence of symptoms. In this study, we present a case of a 59-year old woman, with a descending colon lipoma histologically diagnosed only after surgical resection of the lesion. The approach was adopted according to the patient's clinical picture (intestinal bleeding, vomiting and weight loss), in addition to the occlusion of 80% of the colonic lumen observed in a colonoscopy.